The use of electrophoretic analysis to determine the polymorphism of vegetable bean varieties - E. V. Pankrutskaya; V. V. Skorina (Овощи России, 2023)
Relevance. In Belarus, no full-fledged studies have previously been carried out to identify species diversity, to identify forms of vegetable beans that have similar genetic diversity. The purpose of the research is to determine the number and ratio of biotypes, to identify the level of genetic polymorphism in vegetable bean varieties by electrophoresis of storage proteins.Materials and Methods. The research was carried out at the BSAA in 2021–2022 on soddy-podzolic medium loamy soil. The experience was based on generally accepted methods and guidelines. The objects of research were 42 varieties of vegetable beans (34 - bush form) and (8 - climbing) of Belarusian and Russian selection. Analysis of seed storage proteins in vegetable bean varieties and identification of spectra were carried out according to the methods. To assess the differentiating positions (zones) of the spectrum, identify protein components, and estimate the molecular masses of proteins, standard marker solutions of proteins “Thermo Scientific” – Unstained Protein Ladder (range 5–112 kDa, number of identified proteins – 11) were used.Results. Differences between genotypes were revealed in internal genetic diversity and elements of the protein spectrum of globulins. It has been established that vegetable bean varieties are characterized by hidden genetic variability and a certain level of polymorphism with a different number of biotypes in the structure of the varietal population. In 60% of the analyzed forms, there is a direct relationship between the manifestation of rare, selection-significant components and the degree of complexity of the total component composition of the protein spectrum. This criterion has practical significance and can be used in breeding work with the vegetable bean crop.